Translation and Difference in the Construction of the Reference Curriculum Document of Bahia for Indigenous School Education - Silva, Paulo de Tássio Borges; de Araújo, Rosilene Cruz; Magalhães, José Carlos Batista (ODEERE, 2022)
The proposal analyzes the construction movement of the Reference Curricular Document of Bahia (DCRB) for Indigenous School Education, tensioned by the Bahia Indigenous Education Forum (FORUMEIBA), together with the leaders of the 30 indigenous peoples of Bahia, who punctuated the absence of specific dialogues about Indigenous School Education in the DCRB, approved by the State Council of Education of Bahia in December 2019. The DCRB is an attempt to translate the National Common Curricular Base (BNCC), being created from it, the (Re)Elaboration of Curriculum References in Bahian Municipalities, DCRB translation movements in more than 417 municipalities in Bahia. Thus, operating with the notion of translation (DERRIDA, 2002), in the understanding that policies are not implemented, but translated and interpreted, we seek to understand which curricular landscapes (SILVA, 2019) have been given to Indigenous School Education in Bahia, in the sense of “escaping” from the BNCC, common speech among teachers and indigenous leaders, and producing curricula for difference. The analysis points to attempts at curriculum production in indigenous contexts beyond the BNCC, which has produced resonances in the restriction of difference in Indigenous School Education, making it possible to think about curricula for difference.